Penggunaan konsep margin keuntungan secara ruang dalam menentukan kelebihan lokasi bagi kilang perusahaan roti - Lasimon, Norlia Mazlin (2009)
Location planning is crucial in determining the best site for industrial development. Currently, industrial location planning focuses more on the physical rather than the economic aspects for selecting such locations. This research focuses on the latter, taking bread manufacturing industry as a study case. This research has two objectives. Firstly, to review the theoretical aspects of industrial location. Secondly, to demonstrate how Geographic Information System (GIS) is used to apply the concept of Spatial Margin to Profitability (SMTP) to determine best locations by taking bread manufacturing as a case. Questionnaires were distributed to respondents in the study area to gather data on revenue, cost of materials, operation, management, marketing and transportation. Network analysis was performed using ArcView 3.3 software to calculate bread distribution cost. It was found that the most profitable area for the bread industry was Pelangi with the profit of around RM 0.20 per capita. It was recommended that future research combines the physical characteristics of industry and industrial location’s level of profitability into industrial location planning by using GIS. Besides, it should also consider profit-based industrial location theory to improve industrial location planning.